Radioactive Waste Disposal in the Sedimentary Rocks of Southern Ontario - Russell, D.; Gale, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary This paper is the first published examination of the Paleozoic sedimentary sequence of southern Ontario as a radioactive waste disposal medium. A major asset in siting a repository in such a sequence is the ability to locate zones with favourable geotechnical properties in suitable hydrogeologic environments by application of a large data base to the relatively simple stratigraphie model. A review of the stratigraphy, and the geotechnical and hydrogeologic properties of shales in the sequence reveals several zones of interest for waste disposal purposes. The most significant factor controlling suitability of an area for reposi-tory siting is the regional flow pattern. Asa start in examining this factor, tenhydrostratigraphic units, distinguished by hydrogeologic properties alone, are proposed and used in a first attempt at evaluating the deep flow regime in southern Ontario.